The study of the influence of laser hardening conditions on the change in properties of steels - Idan, Alaa Fadhil І; Akimov, Oleg; Golovko, Leonid; Goncharuk, Olexiy; Kostyk, Kateryna (Eastern-European Journal of Enterprise Technologies, 2016)
Development of new technologies to improve the durability of high-wear parts is urgent. The goal of the study is to investigate the influence of laser processing conditions on the properties of 40, 40Cr and 38Cr2MoАl steels for surface hardening. Comparative analysis of hardness parameters after the through hardening, hardening and tempering, and laser hardening of steels showed that laser hardening improves the hardness by 1.3–1.35 times compared to the through hardening and by 1.7–2.32 compared to the steel hardness after hardening and tempering. The mathematical patterns of the influence of laser beam travel speed on the case depth depending on the steel grade in the form of quadratic and cubic polynomials are found. These patterns allow predicting the case depth values. Microhardness distribution over the cross section in the zone of local laser hardening showed that the highest hardness values for steels correspond to the zone of the most dispersed martensite, further increase in grain dispersion reduces the hardness parameters. Due to the local surface hardening of 40, 40Cr and 38Cr2MoАl steel parts by laser hardening, operational properties of parts in further operation can be improved. This method is suitable for hardening difficult-to-access areas of parts, local contact areas. The hard case is formed through laser hardening, the matrix of the part remains viscous and softer. This combination of properties improves the durability of parts.